A genome-wide association study identifies new susceptibility loci for non-cardia gastric cancer at 3q13.31 and 5p13.1 - Shi, Yongyong; Hu, Zhibin; Wu, Chen; Dai, Juncheng; Li, Huizhang; Dong, Jing; Wang, Meilin; Miao, Xiaoping; Zhou, Yifeng; Lu, Feng; Zhang, Hanze; Hu, Lingmin; et al. (Nature genetics, 2011)
Hongbing Shen, Dongxin Lin, Yongyong Shi and colleagues identify two new susceptibility loci for non-cardia gastric cancer. They also confirm three previously reported risk loci for this gastric cancer subtype. Gastric cancer, including the cardia and non-cardia types, is the second leading cause of cancer-related deaths worldwide. To identify genetic risk variants for non-cardia gastric cancer, we performed a genome-wide association study in 3,279 individuals (1,006 with non-cardia gastric cancer and 2,273 controls) of Chinese descent. We replicated significant associations in an additional 6,897 subjects (3,288 with non-cardia gastric cancer and 3,609 controls). We identified two new susceptibility loci for non-cardia gastric cancer at 5p13.1 (rs13361707 in the region including PTGER4 and PRKAA1 ; odds ratio (OR) = 1.41; P = 7.6 × 10 −29 ) and 3q13.31 (rs9841504 in ZBTB20 ; OR = 0.76; P = 1.7 × 10 −9 ). Imputation analyses also confirmed previously reported associations of rs2294008 and rs2976392 on 8q24, rs4072037 on 1q22 and rs13042395 on 20p13 with non-cardia gastric cancer susceptibility in the Han Chinese population.